Formulation and In Vitro Evaluation of Compressed Coated Tablets of Simvastatin for Pulsatile Drug Delivery: Pharmaceutical Science-Pharmaceutics for Effective Drug Dosage - P.V. Kamala Kumari; V. Mounica; Y. Srinivasa Rao (International Journal of Life Science and Pharma Research, 2022)
Pulsatile drug delivery system is one type of drug delivery system, where the delivery device is capable of releasing drugs after a predetermined time-delay (i.e. lag time). This system has a peculiar mechanism of delivering the drug rapidly and completely after a "lag time," i.e., a period of "no drug release." These systems are beneficial for drugs having high first-pass effect drugs administered for diseases that follow chrono pharmacological behavior such as drugs having specific absorption sites in GIT, targeting to colon; and cases where nighttime dosing is required. The objective of the present study was to formulate and evaluate a press coated pulsatile drug delivery system of simvastatin in order to attain a time controlled release to lower the blood cholesterol level by releasing the drug with a distinct predetermined lag time of five hrs. Simvastatin is a water insoluble drug and its absorption is dissolution rate limited. The core formulations were composed of simvastatin and disintegrants like lycoat, SSG, ludiflash in different ratios and was coated with xanthan gum, guar gum, HPMC K4M, HPMC K15M as a release modifier. Press coated tablets were evaluated for hardness, friability, drug content, and in vitro drug release. Result of in vitro dissolution study of the prepared tablet suggested that, the release of drug from press coated tablets match with chrono-biological requirement of disease.